Social inclusion of rural-rural migrant arable crop farmers and agriculture production in Delta State, Nigeria. Issue 2 (4th May 2019) - Ofuoku, Albert Ukaro
ABSTRACT: This study was conceptualised to determine the influence of social inclusion on rural-rural migrant arable crop farmers' level of agricultural production. A sample of 254 rural-rural migrant arable crop farmers identified by key informants. Findings revealed farmers had a mean age of 45 and were mostly married females who had completed secondary education, had an average of 15 years farming experience. Average farm size was 2.5ha and annual mean crop output ranged from 1000 to 25, 000 kg (1–25 metric tons). Most had membership in farmers' groups and contact with two extension agents monthly. Their level of social inclusion at a community level was lower (inclusion index = 0.68) than at the farmers' group level (inclusion index = 0.85). Social inclusion of rural-rural migrant farmers achieved significance to level of crop output at the farmers' group level. Socioeconomic attributes, such as gender, marital status, level of formal education, years of farming experience in host communities, and monthly extension contact, contributed to farmers' level of social inclusion. It is recommended that social inclusion of rural-rural migrant farmers in their host communities should be encouraged and sustained; social inclusion of migrant farmers in farmers' groups should also be sustained and encouraged by the public agricultural extension agency and related non-governmental organisations, with those in communities that had not subscribed to membership of such groups encouraged to do so.